Role of remote sensing and geotechnical studies in assessing the landslide vulnerability in the Chamoli region of Uttarakhand, India - Shubham Singh; Nirlipta Priyadarshini Nayak; Ashish Aggarwal; Harsh Kumar Verma (Discover Applied Sciences)
Abstract Landslides are the most common of all natural hazards. Climatic changes, increasing population, unplanned urbanisation and increasing connectivity to the hilly regions are the prime contributors to landslides. Chamoli, the second largest district of Uttarakhand state, is home to many pilgrims and tourist spots that are visited by millions every year. It is also a zone surrounded by several thrusts/faults that in association with human interference initiate the risk of landslides and land subsidence in the region. The district holds limited studies related to landslide susceptibility and risk assessment compared to the other districts of the state. Thus, the current review article focuses on comprehensively analysing various remote sensing and geotechnical investigation-based methods deployed for the monitoring, evaluation and prediction of landslide susceptibility and risk in the region of Chamoli. Lack of connectivity, unscientific planning and improper implementation of technologies in past were the factors for not having a proper landslide risk assessment in the zone. Among the various remote sensing and geotechnical investigation-based methods that are being used globally for landslide susceptibility and risk assessment, only a few have been used in the Chamoli region of which the multi-class index overlay techniques and hybrid machine learning methods were the most widely used in the region. Thus, the study area requires more scientific exploration and studies to have a better assessment of landslide susceptibility and risk which couldn’t be possible due to poor connectivity and unavailability of proper data in the past.